The professional profile of music teacher in secondary education: Musical creation from a competence-based approach - Castro-Alonso, Vicente; Chao-Fernández, Rocío (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Music teacher in secondary school assumes a training itinerary that favors the development of technical-musical skills over the didactic-pedagogical ones. This study analyzes the perception of teachers in Galicia regarding their training for musical creation, with respect to the rest of musical, transversal and pedagogical competences. Through an exploratory study through a questionnaire, it is concluded that creation is conceived as one of the least priority aspects, as well as one of the least mobilized in practice. This enables the design of new research and training lines in the field of teacher training.